Aligning Local Conditions with Innovative Waste Solutions: A Study on Community Adoption in Indonesia - Aulia, Wildan; Santosa, Imam; DRSAS, Muhammad Ihsan; Nugraha, Adhi (Journal of Posthumanism, 2025)
Residual waste management in communities faces technical, social, and economic challenges. While participatory approaches have been widely applied, their success is often hindered by varying engagement levels and complex social dynamics, particularly in Indonesian contexts. This study investigates the adoption of multilayer plastic waste processing solutions through a community-engaged design approach in Bekasi, Indonesia. Using action research, it examines how communities interact with proposed solutions, evaluating the technical, aesthetic, and sustainability aspects of processed products, as well as adoption rates. Findings indicate that adoption depends on sustained community involvement, alignment with local conditions, and technical feasibility for independent implementation. By analyzing social dynamics and influencing factors, this research underscores the value of flexible design strategies in enhancing the sustainability of community-based waste management. The study offers actionable insights to improve waste management practices, emphasizing adaptive, context-sensitive solutions tailored to diverse community needs.